Mathematical Games Using Real-World Approaches Increasing Kindergarten Students' Learning Creativity - Choirudin Choirudin; Masrurotul Mahmudah; M. Saidun Anwar; Yuli Ani Setyo Dewi; Dhita Paranita Ningtyas (Journal of Childhood Development, 2021)
Many parents think that games are a waste of time and not useful, so they forbid their children to play, and as a result, the children's soul will be depressed and the words naughty child, cougar, passive, and so on. This assumption is caused by the fact that parents do not fully understand their personality, characteristics, tendencies, and child nature. By looking at conditions like this, Kindergarten is expected to strive to implement the function of play by children's growth and development by providing the freedom to each child accompanied by the cultivation of constructive values Research objectives. To determine the game method's implementation using a real-world approach to increase children's learning creativity in TK Ma'arif 22 Trimurjo. The technique used for this research is qualitative. Subjects were students included and engaged in math games with the real-world: in-depth interview data collection techniques, observation, and documentation. In the implementation of playing activities, students' attitudes are given the freedom to develop their potential and creative power according to their talents and interests. In this case, it can be proven by the games at TK Ma'arif 22 Trimurjo. Mathematical games using a real-world approach in increasing the learning creativity of kindergarten students.